Development of latent fingermarks by unbalanced magnetron sputtering deposited ultra-thin metal film. (December 2021) - Wang, Tao; Zhang, Qiannan; Yu, Shouming; Zhang, Guojun
Abstract: Thin metal films with thickness above 50 nm have been successful used for developing level 1 features of latent fingermarks. In order to easily show the level 2 and level 3 features of the fingermarks, thinner films are needed to be fabricated. Three kinds of metal films including cooper, chromium and aluminum with film thickness ranging from 5 nm to 30 nm were deposited by unbalanced magnetron sputtering. The efficacy of film thickness and metal type on developing latent fingermark was investigated. The most clearly developed fingermark was obtained by films with thickness of 10–20 nm. Cooper films exhibit better effects on showing Level 2 features than chromium and aluminum films with the same thickness. The optical contrast of fingermark ridges and valleys was influenced by the morphology difference of film deposited on ridge and valley areas, which were related to shadowing effect affected by film thickness and metal type determined re-emission effect. Highlights: Latent fingerprints can be development by MS deposited ultra-thin metal films. Level 2 features of latent fingerprint was clearly showed by Cu films. Contrast of fingerprint ridges and valleys dependent on height difference of films.